Inhibition of fruit softening by cold plasma treatments: affecting factors and applications. - Pan, Ya-Wen; Cheng, Jun-Hu; Sun, Da-Wen (Critical Reviews in Food Science & Nutrition, 2021)
Softening is a common phenomenon of texture changes associated with plant cell walls, inducing a decrease in the quality of fruit. Inhibiting the softening is effective to extend the shelf life of fruit. Cold plasma (CP), as a novel nonthermal technology, has been applied to keep the freshness of the fruit. This review centers on applying cold plasma treatments to the inhibition of fruit softening. Different pathways for inhibiting fruit softening by CP treatments, including maintenance of fruit firmness, reduction in the activities of enzymes, inactivation of fungal pathogens and lowering of respiration rates, are discussed. The biochemistry of fruit softening and the fundamental of cold plasma are also presented. In general, among all postharvest technologies, cold plasma is a promising method with many advantages, showing great potential in maintaining the quality and inhibiting the softening of the fruit. Future work should focus on process optimization to achieve better results in maintaining fruit freshness, and commercial applications of cold plasma technology should also be explored.